Enhanced electrochemical and photocatalytic activity of g-C3N4-PANI-PPy nanohybrids (SCOPUS) - ?Sivaranjan Kuppan (Tanjung Malim, 2021)
Enhanced electrochemical and photocatalytic activity of g-C3N4-PANI-PPy nanohybrids (SCOPUS) by ?Sivaranjan Kuppan